The T-LAK Cell-originated Protein Kinase Signal Pathway Promotes Colorectal Cancer Metastasis - Zykova, Tatyana A. (EBioMedicine, 2017)
Approximately 90% of all cancer deaths arise from the metastatic dissemination of primary tumors. Metastasis is the most lethal attribute of colorectal cancer. New data regarding the molecules contributing to the metastatic phenotype, the pathways they control and the genes they regulate are very important for understanding the processes of metastasis prognosis and prevention in the clinic. The purpose of this study was to investigate the role of T-LAK cell-originated protein kinase (TOPK) in the promotion of colorectal cancer metastasis. TOPK is highly expressed in human metastatic colorectal cancer tissue compared with malignant adenocarcinoma. We identified p53-related protein kinase (PRPK) as a new substrate of TOPK. TOPK binds with and phosphorylates PRPK at Ser250 in vitro and ex vivo. This site plays a critical role in the function of PRPK. Cell lines stably expressing mutant PRPK (S250A), knockdown TOPK, knockdown PRPK or knockdown of both TOPK and PRPK significantly inhibited liver metastasis of human HCT116 colon cancer cells in a xenograft mouse model. Therefore, we conclude that TOPK directly promotes metastasis of colorectal cancer by modulating PRPK. Thus, these findings may assist in the prediction of prognosis or development of new therapeutic strategies against colon cancer.